Surveillance of SARS-CoV-2 in Frankfurt am Main from October to December 2020 Reveals High Viral Diversity Including Spike Mutation N501Y in B.1.1.70 and B.1.1.7 - Marek Widera; Barbara Mühlemann; Victor M. Corman; Tuna Toptan; Jörn Beheim-Schwarzbach; Niko Kohmer; Julia Schneider; Annemarie Berger; Talitha Veith; Christiane Pallas; Tobias Bleicker; Udo Goetsch; et al. (Microorganisms, 2021)
Background: International travel is a major driver of the introduction and spread of SARS-CoV-2. Aim: To investigate SARS-CoV-2 genetic diversity in the region of a major transport hub in Germany, we characterized the viral sequence diversity of the SARS-CoV-2 variants circulating in Frankfurt am Main, the city with the largest airport in Germany, from the end of October to the end of December 2020. Methods: In total, we recovered 136 SARS-CoV-2 genomes from nasopharyngeal swab samples. We isolated 104 isolates that were grown in cell culture and RNA from the recovered viruses and subjected them to full-genome sequence analysis. In addition, 32 nasopharyngeal swab samples were directly sequenced. Results and conclusion: We found 28 different lineages of SARS-CoV-2 circulating during the study period, including the variant of concern B.1.1.7 (Δ69/70, N501Y). Six of the lineages had not previously been observed in Germany. We detected the spike protein (S) deletion Δ69/Δ70 in 15% of all sequences, a four base pair (bp) deletion (in 2.9% of sequences) and a single bp deletion (in 0.7% of sequences) in ORF3a, leading to ORF3a truncations. In four sequences (2.9%), an amino acid deletion at position 210 in S was identified. In a single sample (0.7%), both a 9 bp deletion in ORF1ab and a 7 bp deletion in ORF7a were identified. One sequence in lineage B.1.1.70 had an N501Y substitution while lacking the Δ69/70 in S. The high diversity of sequences observed over two months in Frankfurt am Main highlights the persisting need for continuous SARS-CoV-2 surveillance using full-genome sequencing, particularly in cities with international airport connections.